Analysis of Ease of Use and Perceived Risk on Online Purchase Decisions Through Trust as a Mediating Variable in the Perspective of Islamic Economics - Novianti, Irohdathul; Julaihah, Umi (Jurnal Penelitian Ekonomi dan Bisnis, 2025)
The rapid growth of e-commerce has transformed consumer behavior, enabling seamless online transactions. However, perceived risks, such as product uncertainty and fraud, hinder consumer trust. This study examines the effects of ease of use and perceived risk on online purchase decisions, mediated by trust, within the Islamic economic framework. Using a quantitative approach, data were collected from 163 Muslim respondents in Malang City through structured questionnaires. Structural Equation Modeling-Partial Least Squares (SEM-PLS) was utilized for data analysis.The findings reveal that ease of use significantly enhances both trust and purchase decisions, while perceived risks negatively impact trust but influence purchase decisions positively when mediated by trust. Trust plays a critical role in bridging ease of use and perceived risk with purchase decisions. From the Islamic economic perspective, the principles of honesty, transparency, and fairness bolster consumer trust and mitigate risks in online transactions. This study highlights the importance of designing user-friendly e-commerce platforms, ensuring secure transactions, and embedding Islamic ethical principles to foster consumer trust and improve purchase decisions. Future research may explore broader contexts and delve deeper into cultural and religious influences on consumer behavior in e-commerce.